THE WITCHER’S INTERNET MAPS: FAN CARTOGRAPHY, ONLINE COMMUNITIES, AND SPATIAL STORYTELLING - Rodriguez-Amat, Joan Ramon; Atteneder, Helena; Belinskaya, Yulia (AoIR Selected Papers of Internet Research, 2026)
This study examines the role of cartography in $2 transmedia franchise, where the absence of an official map has led to diverse spatial interpretations by fans, game developers, and media adaptations. These maps function as "action spaces" (Abend & Harvey, 2015), shaping perceptions of geography and narrative coherence while also reflecting broader issues of authority and interpretation in fictional world-building. Fan-made maps, game maps, and those from the Netflix adaptation reveal divergent spatial logics, illustrating the performative nature of mapping (Gerlach, 2018) and the participatory processes of online communities.Without a singular, authoritative map (Dodge, 2014), $2 fandom engages in active spatial construction, drawing from textual references and narrative cues. Online platforms such as Reddit, Discord, and wikis serve as arenas for debating accuracy, authenticity, and ownership, reflecting broader crowd-sourced knowledge production (Jenkins, 2006). These discussions not only influence fan engagement but also challenge traditional notions of intellectual property and transmedia authorship (Schiller, 2018).By tracing these cartographic debates and mapping practices across multiple fan platforms, this research updates discussions on authorship, ownership, and participatory culture. It situates fictional cartography within contemporary digital knowledge production, expanding its relevance to transmedia storytelling, crowd-mapping, and internet fandom.